Cryptotanshinone inhibits ovarian tumor growth and metastasis by degrading c-Myc and attenuating the FAK signaling pathway - Guo, Huijun; Zhang, Wenjing; Wang, Jiaxing; Zhao, Guannan; Wang, Yaohong; Zhu, Bing-Mei; Dong, Peixin; Watari, Hidemichi; Wang, Baojin; Li, Wei; Tigyi, Gabor; Yue, Junming (Frontiers in Cell and Developmental Biology, 2022)
Cryptotanshinone (CT), a natural compound derived from Salvia miltiorrhiza Bunge that is also known as the traditional Chinese medicine Danshen, exhibits antitumor activity in various cancers. However, it remains unclear whether CT has a potential therapeutic benefit against ovarian cancers. The aim of this study was to test the efficacy of CT in ovarian cancer cells in vitro and using a xenograft model in NSG mice orthotopically implanted with HEY A8 human ovarian cancer cells and to explore the molecular mechanism(s) underlying CT’s antitumor effects. We found that CT inhibited the proliferation, migration, and invasion of OVCAR3 and HEY A8 cells, while sensitizing the cell responses to the chemotherapy drugs paclitaxel and cisplatin. CT also suppressed ovarian tumor growth and metastasis in immunocompromised mice orthotopically inoculated with HEY A8 cells. Mechanistically, CT degraded the protein encoded by the oncogene c-Myc by promoting its ubiquitination and disrupting the interaction with its partner protein Max. CT also attenuated signaling via the nuclear focal adhesion kinase (FAK) pathway and degraded FAK protein in both cell lines. Knockdown of c-Myc using lentiviral CRISPR/Cas9 nickase resulted in reduction of FAK expression, which phenocopies the effects of CT and the c-Myc/Max inhibitor 10058-F4. Taken together, our studies demonstrate that CT inhibits primary ovarian tumor growth and metastasis by degrading c-Myc and FAK and attenuating the FAK signaling pathway.